Pengaruh Literasi Keuangan, Penggunaan E-Money, dan Pengendalian Diri Terhadap Perilaku Konsumtif Mahasiswa di Kota Batam - Susi Susanti Gari; Argo Putra Prima (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the effect of financial literacy, e-money usage, and self-control on students’ consumptive behavior in Batam City. The rapid development of digital payment systems and the lack of financial management awareness are assumed to encourage higher consumptive behavior among university students. This research employed a quantitative approach using a survey method involving 100 accounting students from five universities in Batam City. The sample was determined using the Slovin formula, and data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that financial literacy and e-money usage have a significant partial effect on students’ consumptive behavior, while self-control does not have a significant effect. Simultaneously, financial literacy, e-money usage, and self-control significantly influence students’ consumptive behavior. The coefficient of determination shows that these three variables explain 20.1% of the variation in consumptive behavior, while the remaining percentage is influenced by other factors outside the research model. These findings highlight the importance of improving financial literacy and managing e-money usage wisely to reduce consumptive behavior among students.